The phenotypic and genotypic spectrum of individuals with mono- or biallelic ANK3 variants - Furia, Francesca; Levy, Amanda M.; Theunis, Miel; Bamshad, Michael J.; Bartos, Meghan N.; Bijlsma, Emilia K.; Brancati, Francesco; Cejudo, Lucile; Chong, Jessica X.; De Luca, Chiara; Dean, Sarah Joy; Egense, Alena; et al. (Clinical Genetics, 2024)
ANK3 encodes ankyrin-G, a protein involved in neuronal development and signaling. Alternative splicing gives rise to three ankyrin-G isoforms comprising different domains with distinct expression patterns. Mono- or biallelic ANK3 variants are associated with non-specific syndromic intellectual disability in 14 individuals (seven with monoallelic and seven with biallelic variants). In this study, we describe the clinical features of 13 additional individuals and review the data on a total of 27 individuals (16 individuals with monoallelic and 11 with biallelic ANK3 variants) and demonstrate that the phenotype for biallelic variants is more severe. The phenotypic features include language delay (92%), autism spectrum disorder (76%), intellectual disability (78%), hypotonia (65%), motor delay (68%), attention deficit disorder (ADD) or attention deficit hyperactivity disorder (ADHD) (57%), sleep disturbances (50%), aggressivity/self-injury (37.5%), and epilepsy (35%). A notable phenotypic difference was presence of ataxia in three individuals with biallelic variants, but in none of the individuals with monoallelic variants. While the majority of the monoallelic variants are predicted to result in a truncated protein, biallelic variants are almost exclusively missense. Moreover, mono- and biallelic variants appear to be localized differently across the three different ankyrin-G isoforms, suggesting isoform-specific pathological mechanisms.
CRIS-Team Scopus Importer:2024-07-19
Keywords: aggressivity; ankyrin-G; autism spectrum disorder; epilepsy; hypotonia; intellectual disability; language delay; neurodevelopmental disorder; sleep disturbances